Spatio-temporal changes and driving forces of reclamation based on remote sensing: A case study of the Guangxi Beibu Gulf - Lu, Jingfang; Zhang, Yibo; Shi, Honghua; Lv, Xianqing (Frontiers in Marine Science, 2023)
Since 2000, coastal reclamation projects have been implemented in the Guangxi Beibu Gulf to alleviate the shortage of coastal land resources. As a result, the reclamation area has increased significantly. In this study, based on the Landsat program, we tracked coastal reclamation in the coastal waters of Guangxi in the 21st century. An indicator system was proposed to assess the driving forces of reclamation synthetically. Our results showed that 98.6 km2 of coastal waters of the Guangxi Beibu Gulf was reclaimed from 1997 to 2017, in which three regions underwent great changes: Fangcheng Bay, Tieshan Bay, and Qiznhou Bay. Furthermore, spatio-temporal changes of reclamation were affected by the combination of population growth, economic development, and marine industry development in coastal cities. These results provide an important historical reference for tracking the human development processes of the Guangxi Beibu Gulf, and also offer some suggestions for the rational allocation of reclamation resources.